Efficient PPA-SiO2-catalyzed synthesis of β-enaminones under solvent-free conditions - Nisar, Muhammad; Ali, Ihsan; Shah, Muhammad Raza; Qayum, Mughal; Zia-Ul-Haq, Muhammad; Rashid, Umer; Islam, Md. Saiful (Multidisciplinary Digital Publishing Institute, 2013)
An efficient method has been developed for the synthesis of β-enaminones under solvent-free reaction conditions using PPA-SiO2 as catalyst. The reaction yields were good to excellent (up to 90%). This methodology affords high selectivity and good tolerance of a variety of different functional groups present on both aromatic and aliphatic amines. In addition, the methodology is environmentally benign and cost-effective due to absence of solvent and easy work-up.